Self-sacrificial leadership, thriving at work, workplace well-being, and work-family conflict during the COVID-19 crisis: The moderating role of self-leadership - Danyu Huang; Hao Zhou (BRQ Business Research Quarterly, 2024)
The COVID-19 crisis has created instability in nurses' workplace well-being (WWB) and work-family relationships. Exploring effective leadership tailored to the needs in a special context is significant to address these issues. Therefore, we examined how the interaction of self-sacrificial leadership (SSL) and self-leadership (SL)-explaining in the integration of conservation of resources and self-determination theories-related to thriving at work (TAW), WWB, and work-family conflict (WFC). A multi-wave questionnaire was distributed to 405 nurses working at a large hospital in China. The results indicate that (1) SSL brought more WWB and less WFC, (2) TAW mediated the correlations between them, and (3) SL stimulated more TAW than did SSL and weakened the influence of SSL on TAW. Alongside improving the understanding of the role of SSL and SL during the COVID-19 pandemic, we facilitate management interventions to practitioners.
Keywords: L20; 650; Self-sacrificial leadership; workplace well-being; work-family conflict; thriving at work; self-leadership